Serious Side Effects Associated with the Administration of Johnson & Johnson COVID-19 Antigens after Immunisation: A Case Report from the Wapinda Health Area (North-Ubangi) in the Democratic Republic of the Congo - Vincent Danvene Gonda; Modeste Ndaba Modeawi; Ruphin Djolu Djoza; Colette Masengo Ashande; Koto-Te-Nyiwa Jean-Paul Ngbolua (Britain International of Exact Sciences (BIoEx) Journal, 2024)
On March 10, 2020, the Democratic Republic of the Congo (DRC) declared the onset of the COVID-19 pandemic. Since then, there have been a total of 95,738 cases, comprising 95,736 confirmed cases and 2 probable cases, with 84,321 recoveries and 1,464 fatalities. Following the guidance of the World Health Organization (WHO), African nations have been actively working to establish and expand vaccination programs. Starting the vaccination campaign in the DRC on April 19, 2021, a total of 10,893,593 individuals, estimated to be 20.18% of the target population, have received vaccines. Among them, 882,106 individuals, or 1.65%, have received their first dose, while 8,576,320 individuals or 15.89% of the target population, and have been fully vaccinated. The Democratic Republic of the Congo aims to vaccinate 53.9 million people against COVID-19, according to the technical response secretariat. This article focuses on the post-vaccination symptoms observed in a resident of the Wapinda sector, Yakoma territory in Nord-Ubangi Province, which has raised curiosity and serves as the subject of discussion.